PENERAPAN METODE PEMBELAJARAN TALKING STICK UNTUK MENINGKATKAN HASIL BELAJAR DI SMP NEGERI 51 MAKASSAR - Ramadhan, Al Azhar; Thahir, Ilyas; Surani; Subaedah; Sampurno, Bambang (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to improve student learning outcomes in Islamic Religious Education through the application of the Talking Stick learning model in class VIII A of SMP Negeri 51 Makassar. This study uses a qualitative and quantitative approach with the type of Classroom Action Research (CAR) referring to the Kemmis and McTaggart model which consists of four stages, namely planning, action implementation, observation, and reflection. The study was conducted in two cycles, where each cycle consisted of two meetings. The research subjects were 31 students of class VIII A. Data collection techniques used observation, interviews, tests, and documentation. Data analysis was carried out descriptively quantitatively and qualitatively through the calculation of average scores and percentage of learning completion. The results showed that the application of the Talking Stick learning model was able to improve student learning outcomes gradually. In the pre-cycle stage, the average score was 68.75 with a learning completion of 34.38% (11 students). After the Talking Stick model was implemented in Cycle I, the average score increased to 75.62 with a completion percentage of 53.12% (17 students). Furthermore, in Cycle II, there was a more significant increase with an average value of 86.87 and a completion percentage of 87.50% (28 students), thus exceeding the established success indicators, namely a minimum of 80% of students achieving the Minimum Completion Criteria (KKM) of 78. In addition to improving learning outcomes, the application of the Talking Stick model also increased student activity, courage, self-confidence, communication skills, and enthusiasm during the learning process. Thus, it can be concluded that the Talking Stick learning model is effective in improving student learning outcomes in Islamic Religious Education subjects in class VIII A of SMP Negeri 51 Makassar.